Severe/combined immunodeficiency in children – a cohort of 19 patients. (24th May 2012) - Jyothi, S; Pollock, S; Guckian, M; Welch, S; Huissoon, A; Hackett, S
Abstract : Background: Severe Combined Immunodeficiency (SCID/CID) is a primary immune deficiency and usually has severe defect in both T- & B-lymphocyte systems. This usually results in onset of one or more serious infections within first few months of life. Aim: Review all cases presented or referred to our immunology department in the past 8 years with suspected immune deficiency. Methods: Case notes, correspondence and results were reviewed for all children diagnosed with SCID/CID at Birmingham Heartlands Hospital in last 7 years. Results: A total of 19 patients were reviewed: 10 males and 9 females were identified. All were born at term and had no antenatal diagnosis of SCID. 9 were born to consanguineous parents and 9 had family history of immunodeficiency. The initial age at presentation varied from 1 day to 24 months. The age at final diagnosis was 2 days to 5 years. Symptoms at presentation included chest infections, diarrhoea, failure to thrive, skin infections and complicated medical problems. 11 were referred to our department for paediatric immunological opinion from other hospitals. 18 of these children were referred for bone marrow transplant to Great Ormond Street Hospital, London or Newcastle-Upon-Tyne Hospitals and 10 have been transplanted to date. 3 are awaiting a donor. One is currently receiving gene therapy and 1 awaiting thymus transplant. 6 of these children did not survive (3 died post transplant and 3 while awaiting transplant) and rest are still under follow up. Conclusions: SCID / CID is a relatively common condition in West Midlands. Presentation of infants with SCID is variable and needs to be considered. Universal screening of Guthrie card heel pricks for T-cell receptor excision circles (TRECs) would allow patients to be identified sooner and hopefully improve survival rates.